Effect of Discectomy on Dynesys Dynamic Fixation in the Treatment of Lumbar Degenerative Diseases - Chen Zhao; Liehua Liu; Lei Luo; Pei Li; Yiyang Wang; Lichuan Liang; Xueping Wen; Dianming Jiang; Qiang Zhou (Pain Research and Management)
Objective. To compare the effect of decompression of the spinal canal with or without discectomy on the clinical efficacy of Dynesys dynamic fixation treatment in lumbar degenerative diseases. Methods. A total of 62 patients treated for single-segment lumbar degenerative disease from October 2010 to November 2017 were retrospectively analyzed. All patients underwent decompression of the spinal canal with Dynesys dynamic fixation and were divided into two groups. Twenty-seven patients in group A did not undergo discectomy, and 35 patients in group B underwent discectomy. The intervertebral height, range of motion, Pfirrmann grade of the surgical segment and the upper adjacent segment, function scores, and operation information were compared. Results. All patients were followed up for an average of 30.7 ± 11.5 months. At the final follow-up, the intervertebral height and range of motion of the surgical segment decreased significantly in both group A and B (p<0.05), the range of motion of the upper adjacent segment increased significantly (p<0.05), and the intervertebral height did not change significantly (p<0.05). The retained percentages of surgical segment intervertebral height and ROM in group A were significantly better than those in group B (p<0.05). The intervertebral height (p>0.05) and range of motion (p<0.05) of the surgical segment in group A were higher than those in group B. The surgical segment Pfirrmann grading of group A was better than that of group B (p<0.05). Conclusion. Dynesys in the treatment of lumbar degenerative diseases may lead to a good clinical effect. In selected cases without discectomy, the range of motion and intervertebral height may be better preserved, and disc degeneration may be reduced.